KEBIJAKAN PEMERINTAH DALAM PEMBERIAN “PROPERTI” BAGI ORANG ASING DI INDONESIA PADA ERA MASYARAKAT EKONOMI ASIA (MEA) - Silviana, Ana (Fakultas Hukum, Universitas Diponegoro, 2019)
ABSTRACT The principle of UUPA is that only Indonesian citizens can own land in Indonesia. Regarding the ASEAN economic sector (MEA) integration agenda, it has an impact on the flow of foreign natural resources into Indonesia to invest. In the land sector, of course it is related to the provision of residential property (